A literature review of rapport management in business meetings - Johari, Danish; Mohamad Ali, Afida; Paramasivam, Shamala (Universiti Putra Malaysia Press, 2015)
A meeting is a planned communicative event where the participants' role is to achieve the discussed objectives. Business English (BE) is often used as the lingua franca for meetings. Studies on BE are becoming a growing interest but there are still limited readily available studies on business meetings, especially on those in the Malaysian context, and even fewer that describe rapport management in meetings. In a meeting, rapport is established when there is a shift in formality in the management of face, sociality rights and interactional goals. This may be the result of the display of the chairperson's power. BE, on the other hand, is used to achieve the communicative purposes that help to promote rapport. By reviewing past studies, this paper explores how the chairperson in local and other cultures establishes rapport through the use of politeness and other communicative strategies in conversational turn-taking. Conversational Analysis (CA) has been used widely to analyse audio and video recordings of meetings as it provides for microanalysis of such turn-taking. Past studies have shown that politeness, small talk, humour and the use of non-verbal expressions are elements of rapport management displayed by the chairperson.